Designers wanted: participation and the user experience in open source software development - Bach, Paula M.; DeLIne, Robert; Carroll, John M. (Proceedings of CHI 09, 2009)
We present design concepts and related mockups that support the user experience for projects hosted on CodePlex, an open source project hosting website. Rationale for the design concepts is grounded in the open source literature and a thirteen-week study with the CodePlex team. We propose that fostering ways to build trust, providing opportunities for merit, supporting crossover of work activities, and supporting user experience (UX) best practices in CodePlex will help dismantle the social and technological barriers for UX and encourage UX designer participation. We address UX designer motivation as a challenge for participation and conclude that the mockups presented are a first step in furthering the user experience in open source software development.